Features of institutionalization of the theory of physical recreation - Sergeev , S. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. In modern conditions of increasing urbanization, physical inactivity, psycho-emotional stress and adverse socio-economic factors, the problem of preserving and strengthening the health of the population is gaining particular importance. In this regard, the attention of scientists, educators and practical specialists to physical recreation as one of the key tools for ensuring the full restoration of a person’s functional state, disease prevention and improvement of the quality of life is increasing. The theory of physical recreation encompasses a complex of knowledge related to the organization of health-improving physical activity in free time from professional activities. Its research is relevant in the context of the deterioration of physical and mental health indicators of the population, which is confirmed by numerous statistical data from international and national organizations. In particular, according to WHO, insuficient physical activity is included in the list of the main risk factors for mortality worldwide. The purpose of the study is to study the genesis and features of the institutionalization of the theory of physical recreation. Material and methods of the study. The study was conducted at the Educational and Scientific Institute «Prydniprovsk State Academy of Physical Culture and Sport» of the Ukrainian State University of Science and Technologies. General scientific methods were used: general philosophical (analysis, synthesis, induction, deduction, analytical methods); specific scientific principles (objectivity, essential analysis), terminological and chronological methodological approaches. Results. In the middle of the 20th century. active scientific developments in recreational issues begin, numerous research institutes and organizations appear in different countries of the world: the National Recreation Association in the USA, the Parks and Recreation Fund in Japan, the International Association for the Development of the Leisure Sector, the German Society for Leisure Problems, the Italian Cultural and Leisure Organization and the National Institute of Public Recreation, the Institute of Management in the Field of Leisure and Entertainment in the UK, etc. The main task of such organizations is the study of leisure and recreational issues. This period can be defined as the institutionalization of physical recreation, because as a result of increased attention from states and government bodies to the problems of its functioning, the constitutions of most Western European countries, which were adopted after the 1970s, declare the right of citizens to engage in sports and recreational activities, and create strategies and programs at both the state and municipal levels. Conclusions. We can talk about several approaches to determining the essence of physical recreation: institutional, systemic, socio-humanitarian, activity approach, which is fixed on the consideration of physical recreation as a component of a broader social phenomenon – leisure. The largest studies of recreation and leisure are conducted in the American contingent, in the countries of Southeast Asia – the Republic of Korea, Japan, New Zealand. Among European countries – France, Germany, Poland, Spain, the Czech Republic, etc. Theoretical understanding of physical recreation is a necessary prerequisite for its further integration into the system of education, health care, social policy and national security. This necessitates the need for in-depth scientific analysis, updating the paradigm of recreational activities, and developing innovative models for its implementation in the context of modern transformation processes.